Examining underutilized jackfruit (Artocarpus heterophyllus) seeds as a potential source of human subsistence in the Byse community, India - Manianga, Amabile; Ekuban, Charles A. A.; Lukambagire, Isaac; Bose, Chinchu; Sabarinath, S. (Frontiers in Sustainable Food Systems, 2024)
The seeds of jackfruit are often overlooked and discarded globally, leading to the underutilization of this valuable resource. This study explored the potential of utilizing underutilized jackfruit seeds as an alternative source of human subsistence by investigating the availability of jackfruit, the utilization and underutilization of seeds at the household level, and the types of subsistence activities in the community. We used a case study of Byse village in Karnataka, India, to understand this topic. A mixed research approach was used. First, a descriptive research design was employed to collect and describe the data, while a correlation design was used to examine the relationships among variables related to jackfruit seed utilization. Second, a bibliometric analysis was conducted to explore global trends in jackfruit seed utilization. The findings indicated that agriculture, particularly arecanut farming followed by paddy rice cultivation, was the primary means of subsistence in the community. While human consumption of jackfruit seeds is statistically significant, it has a detrimental effect on seed utilization in the community (r = -0.295, p = 0.008). The study also revealed that consuming jackfruit seeds in a semidry form had a positive and significant influence (r = 0.345, p = 0.002) compared to eating them in a fresh form. Consequently, more focus could be placed on encouraging the consumption of semidry jackfruit seeds as a preferred option among residents. Despite the abundance of jackfruits, their seeds are rarely used, with a mean utilization score of 1.77. Since jackfruit seeds are limited in their application and are readily available, they could be utilized as an alternative source for sustainable human subsistence.